Rapid debromination of polybrominated diphenyl ethers (PBDEs) by zero valent metal and bimetals: Mechanisms and pathways assisted by density function theory calculation. (September 2018) - Wang, Rui; Tang, Ting; Lu, Guining; Huang, Kaibo; Yin, Hua; Lin, Zhang; Wu, Fengchang; Dang, Zhi
Abstract: Polybrominated diphenyl ethers (PBDEs) undergo debromination when they were exposed in zerovalent metal or bimetallic systems. Yet their debromination pathways and mechanisms in these systems were not well understood. Here we reported the debromination pathways of three BDE congeners (BDE-21, 25 and 29) by nano-zerovalent iron (n-ZVI). All these BDE congeners have three bromine substituents that were located in ortho-, meta- and para- positions. Results demonstrated that BDE-21, 25 and 29 preferentially debrominate meta-, ortho- and para- bromines, respectively, suggesting that bromine substituent at each position (i.e. ortho-, meta- or para- ) of PBDEs can be preferentially removed. Singly occupied molecular orbitals of BDE anions are well correlated with their actual debromination pathways, which successfully explain why these BDE congeners exhibit certain debromination pathways in n-ZVI system. In addition, microscale zerovalent zinc (m-ZVZ), iron-based bimetals (Fe/Ag and Fe/Pd) were also used to debrominate PBDEs, with BDE-21 as target pollutant. We found that the debromination pathways of BDE-21 in m-ZVZ and Fe/Ag systems are the same to those in n-ZVI system, but were partially different from those in Fe/Pd systems. The debromination of BDE-21 in Pd-H2 system as well as the solvent kinetic isotope effect in single metal and bimetallic systems suggests that H atom transfer is the dominant mechanism in Fe/Pd system, while e-transfer is still the dominant mechanism in Fe/Ag system. Graphical abstract: Image 1 Highlights: The debromination pathways of BDE-21, 25 and 29 were elucidated. SOMO of BDE anion can be well correlated with their debromination pathways. Fe/Ag debrominate PBDEs through e-transfer mechanism. Fe/Pd debrominate PBDEs through H-transfer mechanism. Abstract : The mechanisms and pathways of debromination of PBDEs in single metallic and bimetallic systems were elucidated.